Coexistence of innovation and standardization: evidence from the lean environment of business process outsourcing - Zarzycka E.; Dobroszek J.; Lepistö L.; Moilanen S. (Physica-Verlag, 2022)
It has been argued that companies face the challenge of being innovative while at the same time having to standardize and control organizational processes. While management control research has mostly focused on how control supports innovation, the present study aims to improve our understanding of how controls can support the co-existence of process and management innovations with standardization. The paper adopts a single-case study method and analyses the use of a management control system in the context of a business process outsourcing company which faces the simultaneous need for process and management innovation and standardization. The study examines the relationships between different levers of control and their nature to explain how levers of control can create consistent and countervailing reinforcement that supports the co-existence of innovation and standardization. Moreover, we provide an insight into how certain controls, specifically diagnostic and interactive lean controls, combine the levers of control, so creating countervailing reinforcement. We show that the identified reinforcement enables the coexistence of different innovations and standardization at various organizational levels. Thus, the current study contributes to the stream of research on how management controls work collectively, acknowledging their impact on innovation and the concurrent need for standardization.